Development of a Web-Based Journal Information System for Daily Teaching and Learning Activities at SMAN 1 Payung - Marinda, Dina; Hermawan, Hardika Dwi (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to examine the quality of the information system for website-based class daily journals which were developed in the context of digitizing subject teacher journals at SMAN 1 Payung. The purpose of this research is to change the process of processing learning data into a computational system to make it more effective and efficient. The sample in this study were subject teachers who were randomly selected. This study uses the SDLC approach with the waterfall development method. Information system testing in research was carried out using the ISO 9126 testing model. Information system quality testing uses ISO 9126 testing standards in two aspects, namely usability and functionality. Usability data analysis was tested using the Computer System Usability Questionnaires (CSUQ) questionnaire using the Likert Scale as a measurement scale with the questionnaire instrument: Psychometric evaluation and instructions for use developed by IBM as a standard for measuring software in the usability aspect with a score of percentage. While data analysis on the functionality aspect was tested using the Guttman scale based on ISO/IEC 9126 calculation standards. Each instrument that has a value of "Yes" or "No" is a fixed answer. The results of system testing on the functionality aspect are worth 1, which means that the maximum score and usability has a percentage of 93% which is "very high". Based on the test results, the web-based journal information system for teaching and learning activities is feasible to use.